The "Readiness" of Timor-Leste: Narratives about the Admission Procedure to ASEAN. Issue 2 (August 2019) - Seixas, Paulo Castro; Mendes, Nuno Canas; Lobner, Nadine
This article is based on an empirical research with an inductive approach about the admission of Timor-Leste (TL) to Association of Southeast Asian Nations (ASEAN). We examined a corpus of international newspapers ( n = 48) which forms a debate over this case on the Internet. The articles are reproduced in English and are currently the most representative form of debating the membership delay which takes place since 2011. Throughout the observation of our gathered data, we discovered one main narrative that is reproduced by several authors: The Readiness of TL to join the Southeast Asian grouping. Hence, built through three rationalities (preparedness, ambivalence, and conflict), the Narrative of Readiness reveals a common sense among the agents. Built on two constructs, scattered agents and International Online Media, we propose an eventual International Imagined Community in the making. This article raises the possibility that TL plays a test role in the identity of ASEAN, even though the delay of the TL admission to ASEAN still raises further questions.